Legal Assistance to Victims of Sexual Violence in the Perspective of Maqasid Syariah: A Study of UPTD PPA Banda Aceh - Seva Mayasari; Toguan Rambe (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study examines the role of UPTD PPA Banda Aceh in providing legal assistance to victims of sexual violence and analyses it through the perspective of Maqasid Syariah. The research is grounded in the increasing number of sexual violence cases in 2024 recorded by the Aceh Women's Empowerment and Child Protection Office (DP3A), totalling 1,227 cases, comprising 571 cases involving women and 656 cases involving children. The study addresses how legal assistance is implemented and to what extent it aligns with the objectives of Islamic law. This research employs an empirical legal research design with a qualitative approach, based on field data collected from personnel directly involved in assisting at UPTD PPA Banda Aceh. The findings indicate that legal assistance primarily manifests as juridical support and educational guidance, complemented by medical and psychological services to facilitate the judicial process. UPTD PPA Banda Aceh is mandated to fulfil victims' rights during legal proceedings; however, not all rights can be realised due to law enforcement authorities' dismissals of cases under certain conditions. From the perspective of Maqasid Syariah, this role falls under the dharuriyyah, emphasising the protection of essential human interests, including hifdz al-din, hifdz an-nafs, hifdz al-‘aql, hifdz an-nasl, and hifdz al-mal. The study contributes to strengthening the integration of victim protection within the framework of Islamic legal objectives in contemporary legal practice.